PI, Fuzzy Based Controllers for FACTS Devices in Grid Connected PV System - thumu, raghu (International Journal of Integrated Engineering, 2019)
Now-a-days Renewable Energy Sources became an alternative to meet the increasing load demand because they are environmental friendly and also available abundant in nature. Among the Renewable Energy Sources, the Photo Voltaic (PV) System is gaining more attention due abundant availability of solar energy. The Maximum Power Point Tracking Technique is used to extract maximum power from the Photo Voltaic (PV) Array. When there is a need to transfer bulk amount of power from PV Array to Power Grid, the power quality issues, especially the real and reactive power flow problems, are a major concern. In this paper a novel control technique was proposed to control the power flow and to deal with power quality issues that arise when PV Array is integrated with power grid. It consists of a PI controller and Fuzzy Logic Controller (FLC) fed Flexible AC Transmission System device, namely STATCOM, for effective control of real and reactive power flow in grid connected photovoltaic system. The proposed system was simulated by using MATLAB-SIMULINK Tool Box and the results are compared.